2003
DOI: 10.1046/j.1475-1313.2003.00096.x
|View full text |Cite
|
Sign up to set email alerts
|

Experience and training as determinants of grading reliability when assessing the severity of contact lens complications

Abstract: Grading reliability improves statistically with some experience, although perhaps not to a clinically meaningful extent. No added benefit can be derived from supplemental training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…Efron investigated the influence of experience and training on grading reliability and found a tenuous benefit for experience and none for training. 5 Begley et al, 6 in an investigation of corneal staining grading questioned investigators, found that they used different strategies for assigning grades, and found statistically significant differences in outcomes. Further analysis of the present data indicates that different strategies for grading limbal redness may exist among practitioners in the United States, Germany, and Australia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Efron investigated the influence of experience and training on grading reliability and found a tenuous benefit for experience and none for training. 5 Begley et al, 6 in an investigation of corneal staining grading questioned investigators, found that they used different strategies for assigning grades, and found statistically significant differences in outcomes. Further analysis of the present data indicates that different strategies for grading limbal redness may exist among practitioners in the United States, Germany, and Australia.…”
Section: Discussionmentioning
confidence: 99%
“…The philosophy for grading signs, although subject to some generalized categorizing, is highly internalized by an observer 4 and may be difficult to influence or change outside of research settings. 5 Some practitioners may weight toward the most or least severe sign, some may average over the affected area or tissue, and others may discount signs they consider to be within normal limits that other practitioners would note with more severity. 6 Using limbal redness as the example, a patient wearing lowoxygen transmissible soft contact lenses may report that their eyes are red.…”
mentioning
confidence: 99%
“…However, there was no difference in the improvement in grading reliability between the two groups. From this, Efron et al 33 concluded that grading reliability improves statistically with some experience, although perhaps not to a clinically meaningful extent. No added benefit can be derived from supplemental training in terms of grading reliability.…”
Section: Impact Of Experience and Training On Grading Performancementioning
confidence: 99%
“…To examine this, Efron et al 33 conducted a further experiment whereby the influence of experience and training on grading reliability was assessed on a group of subjects with a common knowledge base.…”
Section: Impact Of Experience and Training On Grading Performancementioning
confidence: 99%
“…Additionally, non-optometrists had difficulty in interpolating their grades into 0.1 increments, preferring unit or half-unit steps. Regarding training, a parallel study revealed a slight improvement in accuracy when optometrists were trained in between consecutive sessions, but the results failed to achieve statistical significance 11 .…”
Section: Introductionmentioning
confidence: 99%